Amanah in Tafsir Al-Maraghi: Thematic Analysis and Educational Implications for Islamic Character Education - Syamsuddin, Syamsuddin; Annur, Saipul; Khoiriyah, Ngamilatun; Afriantoni, Afriantoni (AL-ISHLAH: Jurnal Pendidikan, 2026)
Amanah is a central Qur’anic value related to trust, responsibility, justice, and accountability, yet its interpretation in specific tafsir works and its operational relevance for Islamic character education remain underexplored. This study examines the concept of amanah in Tafsir Al-Maraghi and formulates its implications for Islamic character education. This study employed qualitative library research by combining tafsir maudhu‘i, qualitative content analysis, and thematic analysis. Five Qur’anic verses were purposively selected: Q. Al-Baqarah [2]:283, Q. An-Nisāʾ [4]:58, Q. Al-Anfāl [8]:27, Q. Al-Mu’minūn [23]:8, and Q. Al-Aḥzāb [33]:72. The unit of analysis consisted of Qur’anic verses, Al-Maraghi’s exegetical passages, and ethical concepts derived from the interpretation. Data were analyzed through open coding and axial coding to identify major themes. The study found five interrelated dimensions of amanah: entrustment and justice, awareness of betrayal, financial responsibility, fulfillment of promises, and cosmological accountability. In Tafsir Al-Maraghi, amanah is presented as a comprehensive moral obligation involving personal integrity, social responsibility, legal justice, economic honesty, and accountability before God. These findings indicate that amanah can be translated into Islamic character education through learning objectives, Qur’anic-based materials, case-based learning, habituation, reflective practice, assessment rubrics, and school culture. The study contributes a tafsir-based operational framework for integrating amanah into character education, while acknowledging that its practical effectiveness requires further empirical investigation.